Improving Nutritional Content of Bakery Products by Using Orange-Fleshed Sweet Potato Puree - Hossain, M.M.; Rahaman, E.H.M.S.; Heck, S.; Mahmood, S. (2022)
The present experiment was conducted at Super Tasty Food Products Factory, GUK, Gaibandha, Bangladesh 2021. The aim of the study was to improve nutritional content of bakery products by using orange-fleshed sweetpotato (OFSP) puree. Four OFSP and a WFSP varieties were used for making cake and bread at 50%, 30% and 0% substitution levels of wheat flour, respectively. Other ingredients were maintained following standard bread and cake making procedure of the factory. Eleven treatments combinations were used for this purpose. The bakery products thereafter subjected to nutrient analysis and sensatory evaluation. The highest amount of beta carotene content was recorded in T4 treatment (2.91 mg/100g in bread and 1.04 mg/100g in cake) followed by T9 treatment (1.69 mg/100g in bread and 0.63 mg/100g in cake). Iron was noted maximum in T2 treatment (7.46 mg/100g in bread and 5.58 mg/100 in cake). The entire sensory attributes of prepared bakery products were accepted as fair to very good and have no remarkable difference of traditional products of bread and cake. The overall acceptability of the product was observed highest (good to very good) in T9 treatment.